Avaliação do desempenho do irrigâmetro na estimativa da evapotranspiração de referência para as condições da região sul do Estado do Espírito Santo - Barbosa, Venilton Santos (2010)
The present study was carried out with the objective to evaluate the performance of the Irrigâmetro® at estimation of reference crop evapotranspiration in the South Region of Espírito Santo State, during seasons of the year, as well as, to calculate the v